High-quality genome assembly and comparative genomics of Pseudocercospora ulei GCL012, the causal agent of the South American leaf blight (SALB) in natural rubber tree Hevea brasiliensis: Towards the prediction of molecular components associated with its pathogenicity and virulence (2021)
ilustraciones, gráficas, fotografías a color, tablas